Discovery of Small Molecule NSC290956 as a Therapeutic Agent for KRas Mutant Non-Small-Cell Lung Cancer - Zhang, Jiaxin; Liu, Zuojia; Zhao, Wenjing; Yin, Xunzhe; Zheng, Xiliang; Liu, Chuanbo; Wang, Jin; Wang, Erkang (Frontiers in Pharmacology, 2022)
HRas-GTP has a transient intermediate state with a “non-signaling open conformation” in GTP hydrolysis and nucleotide exchange. Due to the same hydrolysis process and the structural homology, it can be speculated that the active KRas adopts the same characteristics with the “open conformation”. This implies that agents locking this “open conformation” may theoretically block KRas-dependent signaling. Applying specificity-affinity drug screening, NSC290956 was chosen by high affinity and specificity interaction with the “open conformation” structure HRasG60A-GppNp. In KRas-driven non-small-cell lung cancer (NSCLC) model system, NSC290956 effectively suppressed the KRas-GTP state and gave pharmacological KRas inhibition with concomitant blockages of both the MAPK-ERK and AKT-mTOR pathways. The dual inhibitory effects led to the metabolic phenotype switching from glycolysis to mitochondrial metabolism, which promoted the cancer cell death. In xenograft model, NSC290956 significantly reduced H358 tumor growth in nude mice by the mechanisms similar to those observed in the cells. Our work indicates that NSC290956 can be a promising agent for the KRas-driven NSCLC therapy.